2010
DOI: 10.2214/ajr.09.3766
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved and Bolus-Chase MR Angiography of the Leg: Branching Pattern Analysis and Identification of Septocutaneous Perforators

Abstract: OBJECTIVE The goal of this study was to compare time-resolved MR angiography (MRA) and bolus-chase MRA in the identification of peroneal artery septocutaneous perforators and for classification of the branching pattern of the arterial tree in the leg in a cohort of candidates for fibular free flap transfer operations. MATERIALS AND METHODS Retrospective analysis was performed on imaging data from 53 legs of 27 patients (age range, 27–88 years) who underwent time-resolved MRA (FLASH; TR/TE, 2.5/1.0; flip angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…None of the cadaveric studies reported hypoplasia or aplasia of the PR, in any of the 791 limbs dissected. On the contrary, the PR was reported to be angiographically hypoplastic (type IV‐A variant) in eight limbs, and aplastic (type IV‐B variant) in four limbs, with overall incidence of 0.14% and 0.07%, respectively (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the cadaveric studies reported hypoplasia or aplasia of the PR, in any of the 791 limbs dissected. On the contrary, the PR was reported to be angiographically hypoplastic (type IV‐A variant) in eight limbs, and aplastic (type IV‐B variant) in four limbs, with overall incidence of 0.14% and 0.07%, respectively (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…In the other two subtypes, the PR shares the blood supply to the foot along with the remaining tibial vessel, and usually has larger diameter suggesting a relative dominance of the vessel . Clinical examination alone may fail to detect these variations, and unlike the Allen's test in the forearm, dominant variant vessels of lower limb cannot be clinically detected before surgery . Harvesting the dPR may potentially place a risk on 10% of patients with anatomical variants.…”
Section: Discussionmentioning
confidence: 99%
“…As such, Sandhu et al investigated the utility of time-resolved magnetic resonance angiography and bolus-chase magnetic resonance angiography in clinical candidates for a free fibula osteocutaneous flap. 5 A total of 53 legs from 27 patients were retrospectively reviewed, with the greatest density of peroneal septocutaneous perforators (82.2 percent) along the distal two-thirds of the fibula.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similarly, two reports did not differentiate their data based on perforator branch types, so these reports were excluded from the musculocutaneous and septocutaneous subgroup calculations. 6,7 Table 1 lists the demographic and study characteristics of the final data group.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In patients who underwent the examination for planning a fibula free-flap transfer operation, the lower resolution examination still allowed proper evaluation of the lower extremity vascular branching patterns and lesion localization, although perforator localization is more accurate with a higher-resolution examination. Repeat examinations were not required in any patient [24]. …”
Section: Discussionmentioning
confidence: 99%